Kuasa dan Wacana: Mengurai Ideologi Politik Pemberitaan Tentang “Peringatan Darurat” pada Detiknetwork - Rohmatulloh, Muhammad Taufiqur; Setiawati, Eti (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study analyzes the construction of discourse and political ideology in the reporting of "Emergency Warning" by Detik Network using Fairclough's critical discourse analysis. Primary data was obtained from Detik Network's news related to “Peringatan Darurat”. The secondary data comes from literature sources regarding Fairclough's critical discourse analysis. Data analysis was carried out through data reduction, data presentation, verification and using a triangulation strategy. The results show that Detik Network shapes public opinion through critical nuanced vocabulary, text representations that emphasize DPR-MK tensions, and discursive practices that strengthen the government's stability narrative. Sociocultural analysis reveals the ideological conflict between participatory democracy and dominant authority (DPR-government). Detik tends to reduce public demands as a temporary phenomenon and obscure structural problems such as oligarchy in the revision of the Pilkada Law. The findings emphasize the importance of media literacy to criticize news bias, media transparency in complex political issues, and the need for further research on the role of the media in democratic dynamics. Practical implications emphasize media accountability in presenting political information objectively. ABSTRAK Penelitian ini menganalisis konstruksi wacana dan ideologi politik dalam pemberitaan "Peringatan Darurat" oleh Detik Network menggunakan analisis wacana kritis Fairclough. Data primer diperoleh dari berita Detik Network terkait "Peringatan Darurat". Adapun data sekunder berasal dari sumber literatur mengenai analisis wacana kritis Fairclough. Analisis data dilakukan melalui reduksi data, penyajian data, verifikasi serta menggunakan strategi triangulasi. Hasil menunjukkan Detik Network membentuk opini publik melalui kosakata bernuansa kritis, representasi teks yang menegaskan ketegangan DPR-MK, serta praktik diskursif yang menguatkan narasi stabilitas pemerintah. Analisis sosiokultural mengungkap konflik ideologis antara demokrasi partisipatif dan otoritas dominan (DPR-pemerintah). Detik cenderung mereduksi tuntutan publik sebagai fenomena temporer dan mengaburkan masalah struktural seperti oligarki dalam revisi UU Pilkada. Temuan menegaskan pentingnya literasi media untuk mengkritisi bias pemberitaan, transparansi media dalam isu politik kompleks, serta perlunya penelitian lanjutan tentang peran media dalam dinamika demokrasi. Implikasi praktis menekankan akuntabilitas media dalam menyajikan informasi politik secara objektif.